Perilaku Kekuatan Baja Tulangan Beton Akibat Kebakaran - Rahman, Rezky; Kurniawandy, Alex; Fatra, Warman (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
In general, when a reinforced concrete suffered a fire, a lot of people tend to replace it with anew reinforced concrete, because they assume that the strength of the element structure isalready changing. Though it is possible to keep re-creating the building by recountingstrength structural elements. The purpose of this studywass to know a changing of yield andtensile strength toward concrete-steel reinforced bar after burning at various temperature.Steel reinforced bar used was 13 mm (S13) and 16 mm (S16) in diameter which is the gradewas (BjTS 40) and (BjTS 35), respectively. The yield and tensile strength as receivedcondition of S13 were 432,02 MPa and 583,62 MPa, respectively, and S16 were 369,38 MPaand 514,58 MPa, respectively. The average yield strength of S13 after burning at 600 °C,800 °C, and 1000°C, were 411,78 MPa, 417,80 MPa, and 428,14 MPa, respectively. And thetensile strength of S13 were 563,64 MPa, 568,83 MPa, and 577,83 MPa, respectively. Theaverage of yield strength of S16 were 346,15 MPa, 358,13 MPa, and 362,28 MPa,respectively. And the tensile strength of S16 were 504,94 MPa, 507,05 MPa, and 518,49MPa, respectively. Based on this result, S13 and S16 concrete-steel reinforced bar beforeand after burning were still in the same grade compare to as rechieved. It can be concludedthat the building after fire at a temperature 600 ° C, 800 ° C and 1000 ° C for 1 hour with 2.5cm concrete cover thickness still meet the strength requirements of the building.Keywords: Reinforced Concrete Steel, Yield Stress (fy), Tensile Strength (fu), Burning